2022
DOI: 10.1002/eat.23680
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating in sexual minority post‐9/11 United States veterans

Abstract: Objective: It is well documented that sexual minority individuals are more likely to report disordered eating (DE) than those identifying as heterosexual. Although DE is prevalent in veterans, investigation of potential disparities in DE among sexual minority veterans is limited. This study examined rates of DE in post-9/11 United States (U.S.) veterans identifying as sexual minorities and explored their association with discrimination because of marginalized identities. Methods: A national sample of recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…For women, prevalence of probable eating disorder diagnosis was notably higher for bisexual women (23,4%) than lesbian women (10%) [ 47 ]. Two studies additionally found bisexual people had higher levels of internalized homophobia compared to lesbian women [ 10 ] and gay men [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…For women, prevalence of probable eating disorder diagnosis was notably higher for bisexual women (23,4%) than lesbian women (10%) [ 47 ]. Two studies additionally found bisexual people had higher levels of internalized homophobia compared to lesbian women [ 10 ] and gay men [ 40 ].…”
Section: Resultsmentioning
confidence: 99%